Reclassification of the serows and gorals: the end of a neverending story?. (29th April 2019) - Mori, Emiliano; Nerva, Luca; Lovari, Sandro
Abstract: Taxonomy is partly a subjective matter, but it is instrumental for ecological, behavioural and especially conservation studies. According to the International Union for Conservation of Nature, goat‐antelopes (Bovidae: Rupicaprini tribe) number 13 species, 62% of which are 'Threatened' or 'Near Threatened' with extinction. During recent decades, the number of extant species of goat‐antelopes – especially in endemic Asian genera (goral: six species Naemorhedus spp.; serow: seven species Capricornis spp.) – has been inflated. We have revised the taxonomy and phylogeny of the gorals and serows, for the first time using the total mitochondrial genome of all taxa. We confirm the existence of three goral and four serow species. We can find no justification for the existence of Naemorhedus griseus (Chinese goral), Naemorhedus bedfordi (Himalayan goral) and Naemorhedus evansi (Burmese goral), which should be pooled together within Naemorhedus goral (brown goral). Two species of mainland serow are also recognised: Capricornis rubidus (red serow) and Capricornis sumatraensis (Sumatran serow). Capricornis rubidus and Naemorhedus baileyi (red goral) are the forms more closely related to the common Pliocenic, still‐unknown ancestor. Among serows, Capricornis crispus is sister to all remaining species. Capricornis rubidus and Capricornis swinhoei (Formosan serow) are sister species, probably the remnants of an older radiation of mainland serows.